The Future of the environment : ecological economics and technological change - Duchin, Faye, 1944-; Lange, Glenn-Marie (Oxford University Press, 1994)
One of the most important and complex challenges facing both developing and industrialized nations is whether they can sustain economic growth without harming the environment. In this timely study, Faye Duchin and Glenn-Marie Lange address this issue in a practical and realistic way: through a detailed evaluation of the well-known approach to sustainable development outlined in the Brundtland Report, Our Common Future. In addition to offering a clear and unflinching look at what development is really doing to the global environment, the unique conceptual framework developed for this analysis provides an invaluable basis for analysis for the new, multidisciplinary field of ecological economics. Duchin and Lange describe how this new methodology will enable economists and policy-makers to evaluate our options for the future and choose those that most effectively reduce environmental degradation and may enable us to achieve sustainable development.